Monitoring the Levels of Cellular NF-κB Activation States - Johanna Meier-Soelch (MDPI AG, 2021)
The NF-κB signaling system plays an important regulatory role in the control of many biological processes. The activities of NF-κB signaling networks and the expression of their target genes are frequently elevated in pathophysiological situations including inflammation, infection, and cancer. In these conditions, the outcome of NF-κB activity can vary according to (i) differential activation states, (ii) the pattern of genomic recruitment of the NF-κB subunits, and (iii) cellular heterogeneity. Additionally, the cytosolic NF-κB activation steps leading to the liberation of DNA-binding dimers need to be distinguished from the less understood nuclear pathways that are ultimately responsible for NF-κB target gene specificity. This raises the need to more precisely determine the NF-κB activation status not only for the purpose of basic research, but also in (future) clinical applications. Here we review a compendium of different methods that have been developed to assess the NF-κB activation status in vitro and in vivo. We also discuss recent advances that allow the assessment of several NF-κB features simultaneously at the single cell level.